Microplastics and endocrine disruption: Emerging risks for human fertility - Anbuchelvan, Subasri Krishnarajan; Udayakumaran, Hashka; Xin, Ang Yu; Loshni, Yoshita; Rashid, Faria (Journal of Biomedical Sciences, 2025)
Background: Microplastics (MPs) and nanoplastics (NPs) are pervasive environmental contaminants that are increasingly recognised for their potential role in endocrine disruption and reproductive toxicity. These particles, ubiquitous in food, water, and air, harbour endocrine-disrupting chemicals (EDCs) and have demonstrated effects on hormonal regulation, gametogenesis, and fertility outcomes in both experimental and observational studies. This short communication highlights current knowledge on the association between microplastic exposure, endocrine disruption, and fertility issues, drawing on recent evidence.